Protocolo mínimo para inventários de répteis Squamata em Estudos de Impacto Ambiental na Mata Atlântica - Moysés, Renan Delpupo (2016)
The first environmental studies in Brazil were made around 1970. Since then, they are getting more important in the national scene. Yet, only in 31st august of 1981, the National Congress approved the Law n. 6.938, which created the Environment National Politics, including the Environmental Impact Assessment (EIA) as an instrument of environmental protection in Brazil. The IBAMA Normative Instruction nº146, of 2007, was created due to establish criteria for proceedings related to the wild fauna management in enterprise’s influence areas and polluting activities. This document became the base to this kind of study. However, the NI nº146 it’s a document of general character, that require adjustments for better comply with the inventories in the many fauna groups in each biome in this country. The Atlantic Forest is the most impacted and densely inhabited biome of Brazil, with only 11% to 16% of his original cover remaining. The diversity of Squamata reptiles in the Atlantic Forest is very high, with around 250 species, giving the idea of its relevance to this animal group in the biodiversity maintenance and environmental balance of its natural environment. This shows the value of the Squamata fauna inclusion in Environmental Impact Assessment. The present study intention was elaborate a standardization proposition of the Squamata reptiles fauna inventories in the Atlantic Forest, attempting to adequate the NI nº146 to this group in that biome, maximizing the collection efforts in fauna inventories through the creation of a minimum protocol of Squamata fauna inventories and a guide to track herpetological profiles of a location. We consulted 17 EIAs filed in the library of the organ responsible for the environment in the Espírito Santo State, to evaluate EIAs that held reptile’s fauna inventories in the Atlantic Forest. The positive and negative points in each EIA were listed. We observed that there isn’t any pattern in relation to the samplings methods, in field effort or in how to analyze the obtained data. We also realized that the same personal was responsible for the reptiles and amphibians inventories, in most cases. These groups are totally different in their taxonomy, sampling and analyzing methods. After the evaluation of the EIAs, specific literature consulting and interviews with professional herpetologists, we created a protocol for Squamata fauna inventories in the Atlantic Forest, emphasizing that: (1) it is indispensable that all faunal inventories must have at least four field campaigns, one for each season of the year, with at least ten days long each; (2) a deep specific literature and herpetological collections consulting is needed due to determinate the species that occurs or may occurs in the area of the enterprise; (3) for the individuals samplings in the field, the inventories must use active search, pitfall traps and at least two additional methods for Squamata reptiles sampling; and (4) the Squamata faunal inventory evaluation must take into account the knowledge already existent about autecology of species, which in the Atlantic Forest domain, means have a vast domain about the natural history literature and ecology of snakes, lizards and amphisbaenians of this biome. Thereby, we believe that the faunal inventories of Squamata from the Atlantic Forest will became more completes, reliable and standardized. Increasing the quality of Environmental Impact Assessments and allowing judgments with better criteria from the federal and state environmental organs about this studies and reports